Implementation of Dynamic IP Blocking Techniques on the Tanungbalai City Library Website - Azrai Sirait; Muhammad Siddik (STMIK Budi Darma, 2021)
Website Tanjungbalai Library, is one of the most visited by people to find the necessary information, not only that, the website is also a place where people exchange ideas and share knowledge. The Tanjungbalai library website server currently does not have security, of course this will have an impact on the security of the existing data on the website, therefore to prevent unwanted things such as theft or hacking of the Tanjungbalai library website here researchers will take advantage of the features contained in cloud-based cpanel software. So that the security of the library's website server will be maximized, at this time there are still many weaknesses and shortcomings found on the library website, later IP visitors who try to damage will be blocked only by utilizing features on cloud-based cpanel. Information that is less tested and accurate will certainly be very disturbing in the decision-making process and in making reports.